Digital public relations in the context of knowledge gap theory - ÖZGEN, EBRU (My University, 2023)
Globalization, technology-driven economic changes, and digital transformation hastened by the pandemic of the previous four years have shown the relevance of digital and conventional public relations. Due to the rapid development of technology and digitalization, which transforms society, this study examines how public relations experts can use digital technology to reduce the information gap in transferring public relations practices and methods. Descriptive analysis, one of the qualitative research methods, was used after a literature review on the information gap hypothesis of digital public relations. In-depth interviews were conducted and public relations experts answered the subject-specific research questions. Public relations, unlike conventional media tools, lowers the information gap owing to digitalization knowledge and abilities, according to studies.
Keywords: Knowledge gap; Digital public relations; Internet; Digitalization; Social transformation